COVID-19 and Its Reflections on SMES in Developing Countries Experience of Sri Lanka - H.M.S.L. Wijeyewardena; WJKVMR Jayawardhane (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
In response to the COVID 19 outbreak, many countries have declared restrictive measures in order to protect their community. Due to imposition of these measures, dramatic losses have occurred in human lives as well as to the economies of countries. The economic disruption caused by the pandemic severely impacted on Micro Small & Medium enterprises (MSMEs)in the affected countries including Sri Lanka. Hence many Sri Lankan entrepreneurs were unable to provide for themselves and their families as a result of partial closures of their daily business operations under travel restrictions being imposed. Soon after the outbreak of the COVID 19 pandemic, the Sri Lankan government began extending financial & other forms of non-financial assistance to MSMEs and their workers as these enterprises are became more vulnerable to negative shocks and to their supply chain, particularly labor supply, and marketing for their goods and services. In order to make necessary interventions on behalf of MSMEs, The National Enterprise Development Authority (NEDA) Sri Lanka together with the Ministry of Industries have conducted a survey to identify how this pandemic impacted on Sri Lankan MSMEs. In this regard an awareness campaign was conducted through newspaper advertisements and the Enterprise Development Officers of NEDA who are located around the country. Responses were obtained through a structured questionnaire and analyzed using the SPSS software. Findings of the survey revealed that majority of the MSMEs have collapsed financially, and they face different challenges in increasing the number of daily customers due to the prevailing situation in the country. Further this study depicts the short term, medium term and the long-term interventions to be taken by the government in order to uplift the affected entrepreneurs from the ceasing their business. Also, the pandemic opened up opportunities to mobilize and widen existing local production due to the depletion of foreign reserves. Therefore, aggressive motivation of research and development organization and universities to begin undertaking research that can bring about commercialized out puts using out of the box approaches by relaxing old and archive laws restricting valuable human assets only to teaching and undertaking primary research by restricting them to venture in to commercial activities.